Quantity Surveying Profession in Indonesia Construction Industry - Muhammad, Fakhri (2020)
Quantity surveying profession is one of the professions engaged in the construction industry. This profession first appeared in one area of the United Kingdom since the 18th century. This research was carried out to discuss and provide insight on the history of the Quantity Surveying profession and the Quantity Surveying profession in the construction industry in Indonesia. Quantity Surveyors play an important role in a construction project. The Quantity Surveying profession first entered Indonesia in the early 1970s, but due to several factors made this profession less developed in Indonesia. Therefore, this research was carried out to investigate the current scenario of Quantity Surveying practice in Indonesia. The objectives of this research is to identify Quantity Surveying practice in Indonesian construction industry and to identify the perception of being a Quantity Surveyor in Indonesia. In this study, the method used is the Quantitative method by using an online questionnaire to obtain the data. The questionnaire has been conducted and has been distributed to Quantity Surveyors who have registered with the Indonesian Association of Quantity Surveyors (IQSI). The data obtained from the questionnaire has been analyzed using Relative Importance Index (RII). The outcome of this research are most of the members that registered with IQSI are not from Quantity Surveying background, most of the members have working experience is more than 5 and 10 years, majority of the members working as Quantity Surveyor in their company, the main factor that affecting less development of Quantity Surveying in Indonesia is lack of institution that provide Quantity Surveying program, the members chose event/seminar is the best way to delivering the information to the public regarding Quantity Surveying, and majority of the members felt it is really important to open Quantity Surveying program at Universities in Indonesia.